Theoretical premises of the impact of artificial intelligence on the international relations and security - Sajduk, Błażej (The Copernicus Journal of Political Studies, 2019)
The article presents the role of artificial intelligence technology in shaping international security. This particular technology is an example of modern technological innovation that can exert a transformational effect on international relations by altering the capabilities of states (in Waltz’s terms) and thus the balance of power in the international system. The argumentation is divided into three sections. The first one focuses on the role technology plays in IR theory. The second one presents how artificial intelligence technology works and discusses its four key features for international security. The third section introduces Charles Weiss’ theoretical concept for rendering interactions between technology and the international system and uses this distinction to elaborate on how AI may influence international relations in the future.